Development of Digital Twin Modeling for Smart Factory using OpenPLC-Based Control System - Mada Jimmy Arifianto; Afianto; Waluyo Nugroho (Politeknik Piksi Ganesha Indonesia, 2025)
This research discusses how to design and develop Digital Twin modeling in a Smart Factory system with an OpenPLC-based control system. The main problems in conventional manufacturing systems are limited production line flexibility, difficulty in monitoring and controlling complex devices, and process visualization that is limited to technical data without a real depiction. Through the design of a laboratory-scale mechanical system, the creation of a control board based on an STM32H7 microcontroller with an OpenPLC platform, and the development of a Digital Twin application using Three.js and Node.js, this research produces a Smart Factory prototype that can be visualized in three dimensions and operated in real time via a local network or the internet. Test results show that the system is able to display sensor conditions, control actuators, and accelerate decision-making with shorter response times. The implementation of this system supports production process efficiency and offers an alternative industrial automation solution that is economical, flexible, and more intuitive in the implementation of digital transformation.